A handicap in Takotsubo cardiomyopathy: dynamic outflow obstruction - Muhammed Keskin; Veysel Ozan Tanık; Ayça Gümüşdağ; Özlem Yıldırımtürk (KARE Publishing, 2016)
Takotsubo cardiomyopathy (TCM) is an unusual form of acute cardiomyopathy showing left ventricular apical ballooning. Patients with hypotension should undergo urgent echocardiography to determine if left ventricular outflow tract (LVOT) obstruction is present. This complication has been described in 10-25% of all TCM patients. That some patients do not survive an acute TCM event underscores the importance of prompt recognition and targeted management of dynamic LVOT obstruction. Described in the present report is the case of a TCM patient with cardiogenic shock, the hemodynamics of which worsened after inotropic agents were administered, alleviated after serum fluid and beta-blocker treatment.